Histories of Admixture - (:unkn) unknown (My University, 2022)
Genetic admixture is an essential mechanism of the biological evolution of numerous species, including Homo sapiens. In this Habilitation à Diriger des Recherche, we investigate Histories of Admixture in human populations, from population genetics theory to data analysis, via anthropological sampling on the field, and development of statistical methodologies. Chapter 1 focuses on how diverse anthropological categorizations of individuals into populations are at the root of anthropological-genetics study-designs, and how they influence sampling protocols and population-genetics methodological choices. To illustrate this, we describe how we built, since 2005, interdisciplinary projects aiming at reconstructing the evolutionary history of Central African populations, and the genetic and linguistic admixture histories of Cabo Verde, respectively. We then elaborate on ethical and deontological issues in anthropological sciences, emerging at the crossroad between anthropological data collection, data privacy protection, and Open Science. Finally, we provide perspectives about categorization challenges in the human paleo-genomics era. Chapter 2 summarizes the methods deployed and results obtained about the demographic and evolutionary history of Central African populations categorized in so-called “Pygmies” and neighboring “non-Pygmies” based on complex historical and ethnological criteria. We show how asymmetric and sex-specific admixture histories and admixture-related natural selection processes shaped observed genetic and phenotypic diversities in the Congo Basin. Chapter 3 presents a theoretical general mechanistic model of historical admixture in hybrid populations. We analytically show that complex admixture processes leave an identifiable signature in the distribution of genetic admixture fractions across individuals. Chapter 4 presents the forward-in-time genetic-data simulator and summary-statistics calculator implemented in the software Me
Keywords: African Research